STUDY ON APPLICATION OF DIGITAL TECHNOLOGIES IN DENTAL PRACTICE - Marina Meleșcanu-Imre; Victor Lorin Purcarea; Mihaela Pantea; Ana Maria Cristina Țâncu (Romanian Society of Oral Rehabilitation, 2019)
ABSTRACT Aim: The purpose of this study was to evaluate the application of digital technologies amongst dental practitioners in Romania. Material and Methods: An online questionnaire (elaborated in order to detect possible factors that determine dentists to use digital dental technology as well as their interest in digital training) was distributed to a representative sample of dentists. The collected data was subjected to a statistical analyze. Results and Discussions: The obtained results pointed out the existence of dissimilarities as regards the use of digital technologies (digital radiography, digital ortopantomography, CBCT, intraoral scanners, CAD/CAM Systems, digital color determination) by various groups of dental practitioners, thus depending on: medical degree, age, gender, workplace location. Conclusions: digital dental technology has been successfully implemented in current dentistry practice in Romania; yet, dental practitioners are still reluctant in application of newest digital technologies, such as intraoral scanning or CAD/CAM systems, although they declared their interest in digital training.